Gut-brain nexus: Mapping multimodal links to neurodegeneration at biobank scale - Shafieinouri, Mohammad; Hong, Samantha; Lee, Paul Suhwan; Grant, Spencer M.; Khani, Marzieh; Dadu, Anant; Schumacher Schuh, Artur F.; Makarious, Mary B.; Sandon, Rodrigo; Simmonds, Emily; Iwaki, Hirotaka; Hill, Gracelyn; et al. (American Academy of Arts and Sciences (AAAS), 2025)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are influenced by genetic and environmental factors. We conducted a biobank-scale study to (i) identify endocrine, nutritional, metabolic, and digestive disorders with potential causal or temporal associations with AD/PD risk before diagnosis; (ii) assess plasma biomarkers’ specificity for AD/PD in the context of co-occurring gut related traits and disorders; and (iii) integrate multimodal datasets to enhance AD/PD prediction. Our findings show that several disorders were associated with increased AD/PD risk before diagnosis, with variation in the strength and timing of associations across conditions. Polygenic risk scores reveal lower genetic predisposition for AD/PD in individuals with co-occurring disorders. Moreover, the proteomic profile of AD/PD cases was influenced by comorbid gut-brain axis disorders. Last, our multimodal prediction models outperform single-modality paradigms in disease classification. This endeavor illuminates the interplay between factors involved in the gut-brain axis and the development of AD/PD, opening avenues for therapeutic targeting and early diagnosis.
Keywords: Alzheimer, Enfermedad de; Parkinson, Enfermedad de; Neurodegeneration; Multimodal integration; Parkinson’s disease; Alzheimer’s disease; Polygenic risk scores; Gut disorders